The Influence of Compensation Perceptions and Green Building Implementation on Job Satisfaction of PT Xxx Business Unit Project Support and Service - Saffanah Haura Dhiya; Hari Susanta Nugraha; Reni Shinta Dewi (Universitas Diponegoro, 2024)
Abstract: The competitive nature of the real estate sector in Indonesia demands continuous improvement to win the competition. This study explores how compensation perception and the implementation of green building affect the job satisfaction of PT XXX Business Unit Project Support and Service employees. Previous research has shown varied results regarding the impact of these factors on job satisfaction, thus highlighting the need for more specific investigation with the company's conditions. A quantitative research approach was adopted using a structured questionnaire distributed to 67 PT XXX Business Unit Project Support and Service employees, selected through proportional simple random sampling. Statistical analysis was conducted using SPSS Ver. 24, focusing on validity and reliability tests, correlation and regression analyses, and significance testing through t-tests and F-tests. Findings indicate that compensation perception and green building implementation significantly influence job satisfaction among PT XXX Business Unit Project Support and Service employees with a contribution of 61.3%. Regression analysis shows a significant positive relationship, indicating that these factors independently and collectively contribute to enhancing job satisfaction. The results emphasize the importance of adopting a comprehensive HR strategy that focuses not only on fair compensation but also on creating a conducive work environment through green building practices. Additionally, this research contributes to broader findings on organizational behaviour and sustainability in the workplace, providing practical implications for management and policy-making.Keywords: compensation; green building; job satisfaction.Abstrak: Sifat kompetitif dari sektor real estat di Indonesia menuntut peningkatan terus-menerus untuk memenangkan persaingan. Studi ini mengeksplorasi bagaimana persepsi kompensasi dan implementasi green building mempengaruhi kepuasan kerja karyawan PT XXX Business Unit Project Support and Service. Penelitian sebelumnya telah menunjukkan hasil yang bervariasi mengenai dampak faktor-faktor tersebut terhadap kepuasan kerja, sehingga menyoroti kebutuhan untuk penyelidikan yang lebih spesifik dengan kondisi perusahaan. Pendekatan penelitian kuantitatif diadopsi menggunakan kuesioner terstruktur yang dibagikan kepada 67 karyawan PT XXX Business Unit Project Support and Service, dipilih melalui klaster proposional simple random sampling. Analisis statistik dilakukan menggunakan SPSS Ver. 24, berfokus pada tes validitas dan reliabilitas, analisis korelasi dan regresi, serta pengujian signifikansi melalui uji-t dan uji-F. Temuan menunjukkan bahwa persepsi kompensasi dan implementasi bangunan hijau secara signifikan mempengaruhi kepuasan kerja di antara karyawan PT XXX Business Unit Project Support and Service dengan kontribusi sebesar 61,3%. Analisis regresi menunjukkan hubungan positif yang signifikan, mengindikasikan bahwa faktor-faktor ini secara independen dan kolektif berkontribusi untuk meningkatkan kepuasan kerja. Hasil menekankan pentingnya mengadopsi strategi SDM yang komprehensif yang tidak hanya fokus pada kompensasi yang adil tetapi juga pada penciptaan lingkungan kerja yang kondusif melalui praktik bangunan hijau. Selain itu, penelitian ini berkontribusi pada temuan yang lebih luas mengenai perilaku organisasi dan keberlanjutan di tempat kerja, menyediakan implikasi praktis untuk manajemen dan pembuatan kebijakan.Kata Kunci: kompensasi; green building; kepuasan kerja.